2019
DOI: 10.1002/ejp.1471
|View full text |Cite
|
Sign up to set email alerts
|

The association between the weight of schoolbags and low back pain among schoolchildren: A systematic review, meta‐analysis and individual patient data meta‐analysis

Abstract: Background The objective of this study was to determine whether carrying a heavy schoolbag is associated to a higher prevalence of low back pain (LBP). Methods A systematic review and meta‐analysis was conducted (PROSPERO, CRD42018077839). Observational studies analysing the relationship between schoolbag weight and LBP, were searched for in 20 electronic databases and 12 specialized journals until February 28th, 2019, without date or language restrictions. All studies which included ≥ 50 subjects aged 9 to 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Some studies suggested that heavy schoolbags could be a risk factor contributing towards musculoskeletal diseases ( Negrini & Carabalona, 1999 ; Dianat et al, 2014 ). On the other hand, a recent systematic review reported that the available evidence does not reveal a relationship between schoolbag weight and LBP among children and teenagers ( Calvo-Muñoz et al, 2020 ). A systematic review by Yamato et al (2018) found that schoolbag characteristics such as weight, design and carriage method do not increase the risk of developing back pain in children and youth, but there is some evidence that the perception of heaviness is associated with back pain ( Yamato et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that heavy schoolbags could be a risk factor contributing towards musculoskeletal diseases ( Negrini & Carabalona, 1999 ; Dianat et al, 2014 ). On the other hand, a recent systematic review reported that the available evidence does not reveal a relationship between schoolbag weight and LBP among children and teenagers ( Calvo-Muñoz et al, 2020 ). A systematic review by Yamato et al (2018) found that schoolbag characteristics such as weight, design and carriage method do not increase the risk of developing back pain in children and youth, but there is some evidence that the perception of heaviness is associated with back pain ( Yamato et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some biomechanical studies suggest that the backpack carriage was associated with changes in body posture and with some biomechanical alterations in walking among children and adults ( Devroey et al, 2007 ; Mackie & Legg, 2007 ; Liew, Morris & Netto, 2016 ). Previous studies have investigated the association between BP and schoolbag characteristics such as weight, type (design), method of carrying ( Yamato et al, 2018 ; Calvo-Muñoz et al, 2020 ). However, the evidence has been inconsistent ( Yamato et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the perceived weight of school bag was not correlated with the weight of school bag as a percentage of body weight but was correlated with the absolute weight of school bag. A recent literature review showed the association between backpack weight and LBP to be inconsistent across studies (19) and that the available evidence does not support that school bags weighing >10 % of the body weight are associated with higher prevalence of LBP among schoolchildren (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Particular covariates have to be taken into account at this age group, and therefore, results from studies on adults cannot be directly extrapolated to adolescents. As an example, the association between LBP and the weight of school bag has been under a continuous debate (32) but hardly considered in the previous studies. Heavy weight carried in school bags can distort the natural spinal curvature in the middle and lower back causing muscle strain and irritation to the spine joints and the rib cage (33) .…”
mentioning
confidence: 99%
“…Also, the factors associated with LBP in children and adolescents are age, female gender, trunk asymmetry, increased height, time spent watching television or using a computer, smoking, competitive sports, depression and emotional factors, history of spinal trauma, and family history of LBP 3,7 . Opinions differ on the role of schoolbags in the occurrence of LBP in schoolchildren 8‐21 . Two systematic reviews agree there is no convincing evidence that certain aspects of schoolbag use increase the risk of LBP, subject to the methodological quality of the studies included in these reviews 12,13 …”
Section: Introductionmentioning
confidence: 99%